TELAAH KOMITMEN PIMPINAN TERHADAP KESIAPAN IMPLEMENTASI SISTEM MANAJEMEN K3 DI PT BANDENG JUWANA, SEMARANG - Putri Nauragesti Salsabilah; Baju Widjasena; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
PT. Bandeng Juwana is one of the food industry companies that employed 655 workers and has a work area with high potential hazards. Based on Government Regulation Number 50 / 2012, companies that have more than 100 workers or high potential hazards should implement Occupational Safety and Health Management System (OSH-MS). However, PT. Bandeng Juwana has not implemented OSH-MS to date. One of the basic principles in the implementation of OSH-MS is commitment. The purpose of this study was to analyze the extent of leadership commitment to the readiness of the implementation of OSH-MS. This research was a qualitative research using an in-depth interview guides and observation sheets. The interviews were conducted to the president director as well as heads of personnel and heads of factories who served as executors of OSH at PT. Bandeng Juwana. The triangulation informant was an accounting and a personnel implementer who was chosen due to his duties and responsibilities related to the readiness of the implementation of OSH-MS and the production plant workers selected based on his work area. The results showed that all informants had knowledge of OSH experience on OSH problem, and perception  of  susceptibility, seriousness, benefit, and barriers  were similar so that the basis of the formation  of OSH communication, which is an installation of safety sign, budget, infrastructure  including fire protection  system, PPE, and sanitation facility and waste treatment. The unavailability of OSH expert resource was the biggest obstacle of the implementation of OSH-MS at PT. Bandeng Juwana can’t be done yet. However, PT. Bandeng Juwana informed that the management would send their workers to join training on general OSH.